PENGARUH LINGKUNGAN SEKOLAH DAN KOMPETENSI PROFESIONAL GURU TERHADAP PRESTASI SISWA MELALUI MOTIVASI BELAJAR SEBAGAI VARIABEL INTERVENING PADA SMAN 2 SEULIMEUM KABUPATEN ACEH BESAR. - Arsalna, Arsalna; Apridar, Apridar; Heikal, Mohd (Universitas Malikussaleh, 2020)
ABSTRACTThe purpose of this study was to analyze the influence of the school environment, teacher professional competence on student achievement through learning motivation as an intervening variable at SMAN 2 Seulimeum Aceh Besar District. This study used two stages of sampling, namely the Proportionate stratified random sampling technique and the simple random sampling technique (simple random sampling) , which amounted to 156 students . The analysis tool uses the SEM ( structural equation modeling ) A MOS method . the study result showed that variables school environment positive and significant effect on student achievement and motivation, professional competence of teachers and a significant positive effect on student achievement and motivation, and learning motivation also has a positive and significant effect on student achievement . To me see mediation analysis of the school environment and teachers' professional competence and a significant positive effect is partially mediated the achievements of students of SMAN 2 Seulimeum Aceh Besar district.Keywords: school environment , professional competence of teachers , motivation to learn , and student achievement. Â